Pedagogical Challenges and Teaching Practices of Multigrade Teachers in Rural Public Elementary Schools - Urma, Christine R.; Callo, Eden C (Advances in Social Sciences Research Journal, 2023)
This research paper focused on the pedagogical challenges and teaching practices of multigrade teachers in rural public elementary schools. The study aims to identify the perceived level of teachers’ pedagogical challenges and teaching practices. The descriptive-correlational design was used to survey the 59 multigrade teachers. Descriptive statistics and Pearson Product Moment Correlation Coefficient were used to identify significant relationship between the teachers’ pedagogical challenges and their teaching practices. The study revealed that teachers’ expertise, teaching and learning process, school instruction, and school resources of the respondents have significant relationships to the teachers’ teaching practices in preparatory activities, instructional delivery, classroom management, and remedial/enrichment activities. It has been concluded that there is a strong relationship between teachers’ pedagogical challenges and their teaching practices. Pedagogical challenges can have a significant impact on a teacher’s ability to effectively deliver instruction and promote student learning. Addressing the pedagogical challenges faced by teachers requires a comprehensive approach that includes professional development opportunities, collaboration, access to resources, improved school instruction, increased school resources, and encouragement of continuous improvement.